Physcomitrium eurystomum Sendtn., a new moss species in the bryophyte flora of Montenegro - Stešević, Danijela (Array, 2020)
In a vegetation survey conducted in the northeast part of Montenegro, Physcomitrium eurystomum Sendtn. was collected. This is a new moss species for the bryophyte flora of Montenegro. The species has a wide temperate-tropical distribution, but its populations are rather scattered. In most European countries, the species is included on the relevant national Red Lists and most recently, it was added to the European Red List of Mosses, Liverworts and Hornworts. In order to expand our knowledge of its distribution in Montenegro, and to assess its IUCN threat status, further investigations are needed.